GENETIC MUTATION INDUCTION OF Monstera adansonii ON VARIOUS MUTAGENS BY DRIPS APPLICATION - Dwi Wahyuni Haswin (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Monstera adansonii has wide leaves with a split pattern on its strands (split leaf), smooth and shiny to create a basic visualization (background filler) in flower arrangements. This study aims to obtain genetic changes using chemical mutagens. Chemical mutagens used were 250 ppm EMS, 400 and 800 ppm streptomycin, 400 and 800 ppm GA3. The observations were performed after treatments on the parameter of amount of chlorophyll, stomata and leaf color changes. The results showed that both streptomycin treatments significantly reduced the plant height and the number of leaves. The application of streptomycin in high concentration (800 ppm) decreased the total amount of chlorophyll content in the leaves and changed the color as well as the shape of the Monstera leaves. All chemical mutagen treatments had no effect on stomatal density and stomatal area. The changes in leaf color and shape occurred in the high concentration of 800 ppm streptomycin treatment, could not detected by SSR marker.